Hakikat Pendidikan dan Pembelajaran, serta Tanggung Jawab dan Kompetensi Guru - Habsy, Bakhrudin All; Satsabhila, Adhelea; Syakilah, Najwa Jihan Fauha; Sanallah, Ahsin Kama’ah (TSAQOFAH, 2024)
The nature of education and learning is a fundamental and complex concept in the world of education. Education and learning are important processes that aid personal development, nurturing individuals' potential, skills and positive characteristics for their own growth and the betterment of society. In general, they have interconnected meanings and purposes, but they also have important differences. The essence of education and learning, explores the nature of these concepts and their impact on teacher responsibilities and competencies. This research aims to investigate the core principles of education and learning, as well as the responsibilities and competencies teachers need to fulfill their roles effectively. This research uses a qualitative method, with a type of literature study method that uses a review method with the source of journals, books, articles, and other scientific works that are relevant to the object of study in this study. The results of this study include (1) The Nature of Education (2) The Nature of Learning (3) Teacher Professional Competence (4) Teacher Professional Responsibility (5) Teacher Quality Improvement (6) Teacher Professional Standards.